Coral diversity and abundance patterns at the West Coast of Sabah: A case study of Kota Kinabalu coral reefs - Fikri Akmal Khodzori; Nor’ashikin Aslam Zuhairi’; Zepri Abdul Muhaimin; Zarinah Waheed; Muhammad Ali Syed Hussein; Gan Sze Hoon; Yee Tong Kiu; Khairul Hisham Hariz; Mazni Muhammad Addin; Siti Nur Hazwani Oslan (ResearchGate, 2024)
The Kota Kinabalu coral reefs are well-recognized as a tourism hotspot, with a protected area of Tunku Abdul Rahman Park (TARP) established to conserve marine life. The park comprises of fve islands (Sapi, Sulug, Manukan, Mamutik and Gaya Islands) with surrounding fringing reefs covering approximately 50km2 . However, rapid urbanization, high coastal development and excessive tourism activities have led to increased sedimentation, pollution, and habitat destruction, which negatively impacted coral conditions and species richness. The present study expands on past research by evaluating the current state of coral conditions, including coral diversity and abundance patterns at 27 reef sites located within and outside the TARP boundary around the Kota Kinabalu coastal waters. The Coral Video Transect method was used for coral surveys, while the Coral Point Count with Excel Extension software was used for coral coverage measurement. The fndings indicate that Kota Kinabalu reefs had a mean live coral cover of 46.9%±3.4, suggesting they were in ‘fair’ condition. A total of 233 species, spanning 70 genera and 16 families of scleractinian corals were identifed across all reef sites. Following recent taxonomic classifcation, coral surveys and past studies revealed 302 species from 74 genera and 18 families of scleractinian corals, with Porites, Fungia and Acropora predominantly found in reef assemblages. Among these, 18 identifed scleractinian species are considered rare, 51 are vulnerable, and 2 are endangered. The current data also recorded three nonscleractinian hard corals and nine soft corals, including 56 new scleractinian species records for the west coast of Sabah. This study concludes that extensive coastal developments and uncontrolled human activities may have negatively infuenced the variations in coral conditions, diversity and abundance in the study area. Implementing proper regulations and policies for long-term coral reef sustainability would help achieve a balance between coastal shoreline development and the well-being of the communities